2020
DOI: 10.1007/s00508-020-01713-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of resistance exercise in prostate cancer patients

Abstract: Purpose The aim of this systematic review is to provide an update on the effects of resistance exercise (RE) in patients with prostate cancer (PCa), with special attention to the effects on sexual health. Methods A systematic search of the literature was conducted in March 2020 using the databases PubMed, MEDLINE, EMBASE, SCOPUS and the Cochrane Library. Only randomized, controlled trials published after 31 December 2016 were included in this update. Additionally, articles from current and previous reviews wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 80 publications
(172 reference statements)
0
17
0
Order By: Relevance
“…Unfortunately, and most probably due to misconceptions of RE and hence the avoidance of the presumed risk of RE, the first studies investigating the effects of RE in cancer patients, regarding the risk of lymphedema in breast cancer patients [11] and the effects of moderate-intensity RE on the quality of life, body composition and muscular fitness in PCaP [12], were not published until 14 years later in 2003. Knowing the effects of RE in healthy subjects, PCaP on ADT seemed at the time to be the perfect target group for RE, meanwhile an assumption supported by ample evidence [13][14][15]. Indeed, the vast majority of studies investigating the effects of RE were conducted on PCaP receiving ADT.…”
Section: History Of Resistance Exercise In Cancermentioning
confidence: 99%
See 3 more Smart Citations
“…Unfortunately, and most probably due to misconceptions of RE and hence the avoidance of the presumed risk of RE, the first studies investigating the effects of RE in cancer patients, regarding the risk of lymphedema in breast cancer patients [11] and the effects of moderate-intensity RE on the quality of life, body composition and muscular fitness in PCaP [12], were not published until 14 years later in 2003. Knowing the effects of RE in healthy subjects, PCaP on ADT seemed at the time to be the perfect target group for RE, meanwhile an assumption supported by ample evidence [13][14][15]. Indeed, the vast majority of studies investigating the effects of RE were conducted on PCaP receiving ADT.…”
Section: History Of Resistance Exercise In Cancermentioning
confidence: 99%
“…Indeed, the vast majority of studies investigating the effects of RE were conducted on PCaP receiving ADT. Specifically, RE alone or in combination with endurance exercise has been shown to improve the body composition, muscle strength, cardiovascular capacity, physical functioning and fatigue of PCaP [13][14][15]. Moreover, the first study on PCaP with bone metastatic disease was published in 2011 [16].…”
Section: History Of Resistance Exercise In Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…A recent meta-analysis of 21 clinical trials in prostate cancer patients reported that exercise, primarily resistance exercise, significantly reduced fat mass by 0.6 kg and increased lean mass by 0.5 kg after a mean intervention period of 20 weeks [89]. Resistance exercise is effective in improving, or at least maintaining, lean mass by counteracting impaired anabolic signal pathways and inhibiting the cellular atrophy mechanism during ADT [90]. Fat mass has been more commonly investigated in patients with breast or colon cancer given the strong links between adipocytokines/obesity-related markers and these cancers [91].…”
Section: Exercisementioning
confidence: 99%